Nivel de conocimiento y uso de la Anticoncepción Oral de Emergencia en adolescentes en la Institución Educativa Emblemática Santa Ana de Chincha Alta en Septiembre a Diciembre 2017 - Cuba Paccori, Yola Yudit (2020)
The following research work shows the relationship between the variables knowledge and use of the AOE in the adolescents of the I. E. E. Santa Ana Chincha Alta; This study is of a quantitative, cross-sectional type. A sample of 131 students from the fifth year of secondary school of the afternoon shift was used, based on the results, the database was made, which determined that 23 (17.56%) students have a high level of knowledge about the AOE , while 75 (57.25%) students have a regular knowledge on the subject and 33 (25.2%) students have a low knowledge of the questionnaire. And in relation to use, some 11 (47.83%) students report not having used the AOE at any time, while 12 (52.17%) students have used AOE at some point. When establishing the relationship between the two, Chi2 was applied, resulting in 6,806 and the significance value of 0.009 (p> 0.05). A statistically significant relationship is established between the variables knowledge and use of the AOE method in adolescents from the Emblematic Educational Institution Santa Ana.